Playing Minecraft Improves Hippocampal-Associated Memory for Details in Middle Aged Adults - Stark, Craig E. L.; Clemenson, Gregory D.; Aluru, Ujwal; Hatamian, Nikki; Stark, Shauna M. (Frontiers in Sports and Active Living, 2021)
Concerns are often raised about the impact that playing video games may have on cognition and behavior, whether gameplay is intense and protracted as with competitive Esports or whether it is more casual gameplay. Work in our lab and others, however, has shown that at least some classes of games can improve memory function. In particular, playing immersive 3D games that provide rich experiences and novelty improve memory on tasks that rely upon the hippocampus in effects that mirror the effects of “environmental enrichment” in numerous rodent studies. Our goal in the present study was to determine whether even modest amounts of gameplay (~30 minutes / day for 4 weeks) would result in improved memory performance in middle-aged adults. Not only is this demographic potentially highly receptive to gaming (they make up a significant portion of Esports viewers and of game players), but interventions in middle age may be a prime time for reducing later age-related cognitive decline. Here, we found that the benefits in middle age paralleled effects previously observed in young adults as playing Minecraft, showing improved memory performance on a hippocampal dependent memory task.